THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE AND ITS IMPACT ON THE FINANCIAL PERFORMANCE OF BANKING INDUSTRY LISTED IN IDX - Lukas, Stephanie; Basuki, B. (Accounting Department,, 2015)
A lot of researches have studied good corporate governance implementation in manufacturing companies; this research, however, is more focusing in banking industry. Since bank holds important key role in the economics, bank needs a good governance to get a good reputation to play its role well. This research was conducted using secondary data obtained from annual reports of banking companies listed in the Indonesia Stock Exchange for the year 2008 until 2012. The data was analyzed using multiple regression method.The result showed that foreign ownership, board size, and external auditor, as corporate governance variables, partially and significantly affect bank financial performance, while large shareholders, government ownership, commissioner size, independent commissioner proportion, and capital adequacy ratio are found to insignificantly affect bank financial performance. Furthermore, firm size as controlling variable, is insignificantly affect the relationship between corporate governance variables and bank financial performance. Keywords: Corporate governance, financial performance, banking industry,agency theory